Magical imaginations: instrumental aesthetics in the English Renaissance - Guenther, Genevieve (University of Toronto Press, 2012)
Conjuration and The Defense of Poesy -- The Demonology of Spenserian Discipline -- Why Devils Came when Faustus Called Them -- The End of Magic: Instrumental Aesthetics in The Tempest -- Epilogue (Kant's Charm)